The Influence of Brand Image and Viral Marketing on Students Purchasing Decisions Mediated by Price - Luh Komang Candra Dewi; Silvia Ekasari; Gusti Noorlitaria Achmad; Aat Ruchiat Nugraha; Mokhamad Arwani (International Journal of Economics Development Research (IJEDR), 2024)
This study looks into and assesses how viral marketing and brand image affect price-mediated purchasing decisions. There are all 2023 Semarang University Faculty of Economics students. By using the Slovin formula on the data, 59 research samples were generated. SPSS is used as part of the data analysis procedure. The results of the study are shown in the SPSS output, and they show that viral marketing significantly affects expenses. Price is significantly impacted by brand image. Viral marketing has a big impact on what consumers decide to buy. Brand perception has a big impact on consumer purchase decisions. Price has a major role in determining what purchases are made. Pricing is a key mediating factor in the relationship between viral marketing and purchase decisions. Furthermore, pricing has a major mediating role in the link between brand perception and purchase behavior.